Protecting the Good Name of the Nation as Memory Law - Baranowska, Grazyna (European Constitutional Law Review, 2023)
Memory laws - Protecting the good name of the nation - de facto memory laws - Prohibiting statements about the past - Article 301 of the Turkish Criminal Code - Protecting the good name of Poland and the Polish nation - Protecting the good name of the nation as de facto memory laws - Role of organisations in implementing the laws - Rule of law - Independence of the judiciary - European Court of Human Rights - Chilling effect - European memory politics.
CRIS-Team Scopus Importer:2024-08-12